2007
DOI: 10.2320/matertrans.48.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Li Addition on Synthesis of Mg-Ti BCC Alloys by means of Ball Milling

Abstract: The effect of Li addition to Mg on synthesis of Mg-Ti BCC alloys by means of ball milling was studied. Mg-x at%Li (x ¼ 4; 20; 46) alloys prepared by the induction melting method consisted of the HCP phase (Mg-type), the HCP phase + the BCC phase (Li-type) and the BCC phase, respectively. Lattice parameters of the HCP phase decreased with the increase in x, whereas those of the BCC phase at x ¼ 20 and 46 were smaller than that of Li. Mg-x at%Li (x ¼ 4; 20; 46) alloys and Ti were milled for 50-200 h in an argon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
3
41
0
Order By: Relevance
“…Borsa et al reported that a Mg-Ti alloy with the hcp structure is formed by co-sputtering of Mg and Ti in Ar atmosphere [18]. Asano et al [19][20][21], Rousselot et al [22], Calmak et al [23] and Maveja et al [24] reported that several metastable phases with bcc, fcc and hcp structures are formed in the Mg-Ti system by application of high-energy ball milling to Mg and Ti powders in Ar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Borsa et al reported that a Mg-Ti alloy with the hcp structure is formed by co-sputtering of Mg and Ti in Ar atmosphere [18]. Asano et al [19][20][21], Rousselot et al [22], Calmak et al [23] and Maveja et al [24] reported that several metastable phases with bcc, fcc and hcp structures are formed in the Mg-Ti system by application of high-energy ball milling to Mg and Ti powders in Ar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of magnesium, the deformation is mainly by basal plane slip (0001)< −12-10> while for titanium twinning deformation is more important [65]. In one investigation, Asano et al had the idea of adding lithium to magnesium in order to reduce the yield stress of magnesium and also to decreases its lattice parameter [65]. They found that by adding Li to Mg the deformation of Mg was easier and the Ti crystallite size was reduced.…”
Section: Mg-based Bccmentioning
confidence: 99%
“…Although both Mg and Ti have a hexagonal closed packed (HCP) structure, during milling of a Mg and Ti mixture they react differently. In the case of magnesium, the deformation is mainly by basal plane slip (0001)< −12-10> while for titanium twinning deformation is more important [65]. In one investigation, Asano et al had the idea of adding lithium to magnesium in order to reduce the yield stress of magnesium and also to decreases its lattice parameter [65].…”
Section: Mg-based Bccmentioning
confidence: 99%
See 2 more Smart Citations